The Effect of Knowledge Workers’ Types in Strategic Renewal Processes An exploratory study of sample views of academics at Duhok polytechnic university - Odish, James (Humanities Journal of University of Zakho, 2020)
This research aims to identify the types of knowledge workers from the academic staff at Duhok Polytechnic University and their impact on strategic renewal. To reach it, the researcher formulated questionnaire questions related to the types of knowledge workers (the independent variable) and the strategic renewal (the dependent variable), which were randomly distributed (286) to the academic staff working in the colleges and institutes of Duhok Polytechnic University, and (208) valid forms for analysis were obtained. To ensure the validity and reliability of the questionnaire the research use (Cronbach Alpha) and present it to professionals in this field. After testing the hypotheses through conducting the necessary statistical analyzes, the research reached a number of conclusions, the most important of which is the possibility of Duhok polytechnic university relying on all types of knowledge workers as an important means to achieve strategic renewal, while, the most important recommendations was, the Duhok polytechnic university must realize that strategic renewal requires it to take care of all types of knowledge workers.